Proposição de técnica para confecção de corda cirúrgica - Bello, Lucas Krusch (2019)
The most tension resistant, non-metallic, surgical suture is 5 polyester. Still, it’s load represents 9,32% of canine cranial cruciate ligament’s resistance and 5,86% of canine gastrocnemius tendon’s up until it ruptures. In this study, surgical sutures were grouped and twisted, resulting in a rope with high mechanical resistance. We analyzed manufacturing methodology, final conformation and tension resistance, based on three sutures models: “A” (1 polyglactin 910), “B” (1 polyester) and “C” (5 polyester). Considering averages of thickness and final load, the “B” implants obtained lower values than “A”, indicating that polyglactin 910 ropes are more resistant than those of polyester. Moreover, the “C” implants resulted in the highest values of load and thickness, indicating that final thickness is predictive towards tension resistance. Size 1 Polyester was the only one to generate linear regression for supported load, ensuring the 25,34 Newtons (N) increment to every suture added to the implant, wich suggests its use for the creation of non-absorbable ropes. The use of 1 polyglatctin 910 promotes load averages superior to 1 polyester, therefore, it is indicated for making absorbable surgical ropes.